Annual Report on Exchange Arrangements and Exchange Restrictions 1981. (Annual Report on Exchange Arrangements and Exchange Restrictions, 1981)
This paper describes declining activity that was responsible for a weakening of import demand in the industrial countries. There was also a marked reduction in the growth of the volume of imports by the non-oil developing countries, notwithstanding a substantial increase in external borrowing at higher costs and a considerable reduction in the real value of their international reserves arising mainly from rapid inflation. The current account positions of a number of industrial and non-oil developing countries thus became increasingly difficult in 1980. In an overall setting of excess capacity and rising unemployment, demands for protectionist measures in industrial countries intensified during the period under review.